Examination of the Influence of Cognitive Behavior Therapy Components, Consumer Satisfaction and Engagement in Mothers Referred for Drug Abuse and Child Neglect on Treatment Outcomes. Issue 6 (November 2021) - Plant, Christopher P.; Donohue, Bradley; Freeman, Andrew J.; Allen, Daniel N.
Psychological interventions for child maltreatment have predominately been limited to family-supported, multi-component behavioral therapies. Although these comprehensive programs have resulted in positive outcomes, they are relatively costly and there is limited information available as to how the components of these programs influence treatment outcomes. In this study, the CBT components of an evidence-based treatment for child neglect and drug abuse (Family Behavior Therapy) were examined in regards to consumer preferences, consumer engagement and treatment outcomes. Thirty-five mothers identified for child neglect and drug abuse were administered various CBT components successively and cumulatively based on their preferences. Repeated measure ANOVAs indicated that participants chose to receive components that were specific to managing antecedents to drug abuse and child neglect most frequently, followed by parenting skills training, communication skills training, and job/financial skills training. No differences were found in treatment providers' ratings of the participants' engagement across intervention components throughout treatment. Participants rated the intervention components as similarly helpful. Partial correlations revealed that participants' ratings of helpfulness and provider ratings of participants' engagement were not associated with improved drug use outcomes at 6- and 10-months post baseline. Participants' ratings of helpfulness were associated with child maltreatment outcomes at 10-month post baseline, and provider ratings of participants' engagement were associated with child maltreatment outcomes at both 6- and 10-month post baseline. Participants identified for neglect not related to drug exposure in utero improved at a higher percentage than did participants identified for in utero drug exposure, and receiving behavioral intervention components more frequently led to greater percentages of participants improving in both drug use and child maltreatment outcomes.